Personality, Coping Strategies and Youth Problems in Engineering Students - Bahl, Regina; Gupta, Dr. Shubhangi (KnE Social Sciences, 2022)
The major aim of the present study was to assess “Personality, Coping Strategies and Youth Problems in Engineering Students.” A sample of 80 engineering hostellers from Manipal University Jaipur, aged between 18-21 years were selected using the purposive technique of sampling. Big Five Inventory BFI [9] , Coping Strategies Inventory CSI [28], and Youth Problem Inventory YPI [17] were used to assess the variables in the study. The obtained data were analyzed using the statistical technique of Pearson Correlation. The findings revealed that a significant relationship exists between personality and coping strategies. But each personality dimension does not have a significant relationship with each of the youth problems (family, personal, educational, and socio-emotional). Also, no significant relationship has been found between coping strategies and youth problems. However, a significantly negative relationship has been found between problem-focused engagement and personal problems. Keywords: personality, coping strategies, youth problems, engineering students